KUALITAS STIMULI DALAM PENELITIAN EMOSI - Johana E. Prawitasari (Faculty of Psychology, Universitas Gadjah Mada, 1998)
This study is part of a continous effort in developing a theory of emotion from the perspective of indonesia people. The shortcoming aim of this study is to select qualified photograps of facial expressions and gestures of people from west and center sides of indonesia juries were 39 psychologist. They selected photos according to a list of question regarding ethnicity, gestures and facial expression of emotions. Frequency an analysis indicates that only 4 photos out of 16 are qualified as stimuli for studies in ethnical background and facial espression of emotion